MEDIA AMBIENT SEBAGAI MEDIA PERIKANAN DI INDONESIA - Zulfa Rahmawati (Akademi Seni dan Desain Indonesia Surakarta, 2014)
In the bustling media advertising appearing either through print, electronic, digital, through the internet, the media appears iklanunik as alternative choices in advertising media, the ambient media. Media Ambient boredom arose because the traditional advertising media are usually found in every place both on the road, at home, or in a shopping center. The concept of ambient media is outdoor media. Media ambient ertama appeared in London and the country design style influence to our country Indonesia. Many companies use this concept with the help of advertising agencies in Indonesia. Ambient medium term is rarely known to the public except those who know or understand or unusual in the world of advertising.